Critical trends in transnational cinema: Inter-Asian productions and exchanges. Issue 3 (1st December 2020) - Yang, Yanling; Clini, Clelia; Dasgupta, Rohit K.
ABSTRACT: In light of the shift from the first phase to the second phase of transnational cinema studies, this special issue aims to examine a set of practices of transnational cinema that have been taking place within South and East Asia. In exploring transnational cinema activities in the form of transnational remakes, co-productions, cross-contamination of genres, diasporic and (post)colonial cinemas, as well as contemporary documentary film festivals, this issue puts the spotlight on critical trends in transnational cinemas occurring beyond the Western spheres of influences. Focusing on practical applications of case studies across China, Korea, India and United Arab Emirates, this special issue contributes to the debates on the definition and practical applications for research on transnational cinema studies.